The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0366-69132018643702296
|View full text |Cite
|
Sign up to set email alerts
|

Maquiagem mineral desenvolvida a partir de argilas bentoníticas naturais e tratadas organofilicamente

Abstract: INTRODUÇÃOAs argilas são minerais terrosos que apresentam fina granulometria e característica plástica, o que promove maior facilidade em moldá-la quando em contato com água. Possuem em sua constituição química o óxido de alumínio, óxido de silício e alguns óxidos de metais alcalinos e alcalinos terrosos [1]. Na natureza estes materiais são encontrados em abundância e não são materiais de alto custo, isto é, além do baixo custo estes apresentam também fácil acesso. Paralelo a estes fatores, apresentam caracter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The images show the absence of bacteria, demonstrating that there was no risk of bacterial contamination in any of the clays studied that may compromise the system, making them biologically safe and without antimicrobial activity. The same results were obtained in [20,23,26], using cosmetic formulations based on bentonite clays.…”
Section: Samplesupporting
confidence: 78%
See 1 more Smart Citation
“…The images show the absence of bacteria, demonstrating that there was no risk of bacterial contamination in any of the clays studied that may compromise the system, making them biologically safe and without antimicrobial activity. The same results were obtained in [20,23,26], using cosmetic formulations based on bentonite clays.…”
Section: Samplesupporting
confidence: 78%
“…Studies on this subject in the literature are scarce, only being found in books containing technical definitions of the chemical composition of clay. Few papers on its therapeutic and aesthetic uses can be found [5,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Papers about clay are dedicated almost exclusively to other areas, forgetting about other possible alternatives of using the clay.…”
Section: Introductionmentioning
confidence: 99%
“…Bentonite production, for example, is among the 10 most present and exploited minerals in northeastern Brazil. The economic importance of bentonites is due to their numerous industrial applications [2,3], such as use in cosmetics [4,5], pharmaceutical products [6,7], drilling fluids [8,9], as adsorbents [10,11], waterproofing dams and landfills [12], etc.…”
Section: Introductionmentioning
confidence: 99%